Tratamento de água residuária oriunda do processo de lapidação e polimento de vidro - Dalla Vecchia, Paula (2012)
The increasing demand of water used in the industrial sector has led industries to assess the possibilities of internal reuse. The reuse of water is considered a safe and reliable technique involves less investment in the industrial sector and encourages a practice increasingly accessible. The aim of this work is to propose a system of treatment and reuse of wastewater coming from the process of cutting and polishing of glass of a company's trade glasses, based on optimization of the best efficiency, in order to choose the most appropriate type of treatment for wastewater in question due to their physicochemical characteristics and its treatability. The wastewater comes from a trading company called Glass Industry and Trade Fratta Glasses LTDA, located in the town of Pato Branco, PR. The generation of the wastewater occurs in the stage of cutting and polishing the glass, where significant quantities of water are used for cooling and lubricating the abrasive material used in the process. The results suggest that the physicochemical process based on flocculation/settling the basis of alum and anionic polyelectrolyte is the most efficient for treating the effluent under study have been reached maximum levels of removal of BOD, COD, turbidity and silica of about 83.7, 34.0, 99.9 and 60.1%, respectively. Tests on the filters bag shown that this alternative is not compatible with the type of effluent under study, presenting lower removal efficiencies. The low efficiency of this process decreased, consequently, the efficiency of the integration process, where the bags were used in filtration after coagulation / flocculation. Although the physicochemical process of flocculation with polyelectrolyte help provide good removal efficiency of physical and chemical parameters, there are still patterns that do not reach the levels required by environmental legislation, such as aluminum and dissolved solids. Studies should be conducted to identify inorganic material which is responsible for the high concentration of solids and what procedures should be made for efficient removal of both solids loading as the aluminum concentration. Essays optimization, based on multivariate factorial design studies should be performed to the suitability of such parameters and to identify the levels of reuse.